***[RETRACTED]*** Relation of Brand Equity and Word of Mouth Toward Purchase Intention in Surgery Speciality Hospital - Adhyka, Nurmaines; Lita, Ratni Prima; Semiarty, Rima (Unnes Journal of Public Health, 2019)
RETRACTION TO: Adhyka, N., Lita, R.P., & Semiarty, R. 2019. Relation of Brand Equity and Word of Mouth Toward Purchase Intention in Surgery Speciality Hospital. Unnes Journal of Public Health, 8(1): 57-63.   This article has been retracted by Publisher based on the following reason: Based on clarification, authors of the above paper have admitted submitting this paper to another journal which it is forbidden and already explained explicitly in submission form of Unnes Journal of Public Health.   One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.